Direct drive wave energy array with offshore energy storage supplying off‐grid residential load. Issue 9 (8th June 2017) - Sousounis, Marios Charilaos; Gan, Leong Kit; Kiprakis, Aristides E.; Shek, Jonathan K.H.
Abstract : Current developments in wave energy conversion have focused on locations where the wave energy resource is the highest; using large devices to generate hundreds of kilowatts of power. However, it is possible to generate power from low power waves using smaller wave energy devices. These lower rated wave energy converters can form arrays to supply power to remote coastal or island communities which are off‐grid. This study introduces wave‐to‐wire modelling of wave energy arrays for off‐grid systems using low power permanent‐magnet linear generators (PMLGs). Offshore energy storage at the DC link is added to keep the voltage constant along with a current controller for the inverter in order to supply constant low harmonic power to the residential load connected off‐grid. Simulation results produced in MATLAB/Simulink environment show that the wave energy array can generate power independently from the residential side by keeping the system stable using offshore storage. In addition, two different types of controllers for wave energy devices that use PMLGs are compared based on the power captured from the waves.